2018
DOI: 10.9791/ajpanz.2018.07
|View full text |Cite
|
Sign up to set email alerts
|

Internalised Racism

Abstract: This article identifies and explores how the internalised racism of racial minority clients is identified and treated clinically by white psychotherapists. Four psychotherapists, who selfidentified as “white”, participated in semi-structured interviews, exploring their perceptions and understandings of how internalised racism and racism manifested within the clinical setting. The data from these interviews was analysed using thematic analysis and produced four main themes: manifestations of internalise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
2
1
Order By: Relevance
“…This lack of workplace evidence is despite verification that M aori employees face cultural demands in the Aotearoa/New Zealand workplace that appear unique (see Haar and Martin, 2022) and face discrimination in general (e.g. Ellis, 2021). Overall, the present study found workplace discrimination levels that were similar between M aori and Pacific employees (M 5 2.33 v. 2.38).…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…This lack of workplace evidence is despite verification that M aori employees face cultural demands in the Aotearoa/New Zealand workplace that appear unique (see Haar and Martin, 2022) and face discrimination in general (e.g. Ellis, 2021). Overall, the present study found workplace discrimination levels that were similar between M aori and Pacific employees (M 5 2.33 v. 2.38).…”
Section: Discussioncontrasting
confidence: 68%
“…However, empirical workplace evidence is limited in Aotearoa/New Zealand, despite media reports of racism against M aori (e.g. Ellis, 2021) and Pacific peoples (Carroll, 2021). While a metaanalysis exists around the detrimental impact of workplace discrimination on work and wellbeing outcomes (Dhanani et al, 2018), there is a lack of empirical evidence of workplace perceived discrimination from New Zealand minorities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation